Design basics : 3D - Roth, Richard; Pentak, Stephen (Cengage, 2013)
Filled with examples from nature, art, architecture, design, the crafts, and popular culture, this book illustrates the elements of 3D design. It features visual examples from various cultures and presents each concept in full-color